2018
DOI: 10.1542/peds.2018-1457
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Intervention to Improve HPV Vaccination: A Cluster Randomized Trial

Abstract: BACKGROUND: Human papillomavirus (HPV) infection can lead to serious health issues and remains the most common sexually transmitted infection. Despite availability of effective vaccines, HPV vaccination rates are suboptimal. METHODS: In a cluster randomized trial, an intervention used to target parents of adolescents (11-17 years) eligible for a dose of HPV vaccine, was tested in pediatric clinics part of an urban health system. Parents watched a digital video outlining the risks and benefits of vaccine using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…A randomized cluster trial, parents of 11-17 years old girls watched a digital video outlining the risks and benefits of the vaccine was conducted in Indiana, United States. It showed that adolescents whose parents watched the video had a 3-times higher odds of receiving a dose of the HPV vaccine [31].. Another study assessing the effect of a school-based HPV vaccination program used video presentation, and a website for girls 9-14 years old and their parents was conducted in Hongkong. The program resulted in a higher uptake of the HPV vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized cluster trial, parents of 11-17 years old girls watched a digital video outlining the risks and benefits of the vaccine was conducted in Indiana, United States. It showed that adolescents whose parents watched the video had a 3-times higher odds of receiving a dose of the HPV vaccine [31].. Another study assessing the effect of a school-based HPV vaccination program used video presentation, and a website for girls 9-14 years old and their parents was conducted in Hongkong. The program resulted in a higher uptake of the HPV vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
“…Though educational interventions aimed at parents have generally shown limited impact, 24 one recent study indicated benefit to educating parents through tailored videos during medical visits. 25 Culturally tailored interventions also show promise, though more research is needed. [26][27][28] In the era of social media, respected public health organizations with an online presence aimed at parents are also important for changing perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…As the authors aptly point out, the logistics of delivering such an intervention were substantial. 5 Only 1 of 4 patients who were eligible to receive the intervention actually did so. This low level of engagement arose from difficulties in integrating an iPad-based intervention into the clinics' workflow, a challenge that has been reported by many others attempting to integrate mobile health technologies into primary care.…”
Section: University Of Colorado Denver Denver Coloradomentioning
confidence: 99%